The Church's Rejection in Cilegon: The Perspective of Freedom of Religion - Adzimi, Muhammad Wildan Ramadhan; Al-Fatih, Sholahuddin (Hang Tuah Law Journal, 2025)
Freedom of religion is a right guaranteed by law, including the right to establish places of worship for the safe and peaceful practice of religion. Given the potential for conflict between religious communities, the government must accommodate these needs fairly and without favouring any particular group. This study aims to analyse the application of freedom of religion in the establishment of houses of worship in Cilegon City based on applicable laws and regulations and to find a fair solution for all parties in order to create a more inclusive and effective policy to ensure the right to worship for all citizens without discrimination and not to create conflict between religious communities. In conducting this research, a normative research method was used, namely by analysing existing and applicable laws and regulations, then reviewing how they are applied in society. In this case, it was found that there are values in the regulations that do not apply in society, namely that there is rejection in the establishment of houses of worship of certain religions by the surrounding community. On the other hand, an in-depth analysis is needed and the aspirations of the rejecting community must be accepted so that justice is created and does not cause conflict between religious communities.